Dampak Jangka Pendek Program Bahan Bakar Minyak Satu Harga terhadap Biaya Transportasi di Daerah Tertinggal Indonesia - Simatupang, Thamrin Prima (Jurnal Kebijakan Ekonomi, 2023)
This research aims to know the short-term impact of the One Price Fuel program implemented in 2017 on transportation cost in underdeveloped areas of Indonesia. Observation is conducted to 585 villages since 2006, 2014 and 2018 with a total observation unit of 1,755 villages. With Difference-in-Difference analysis method, this study shows the program has a significant impact on reducing transportation costs in villages that are a radius of 15 km from the gas stations (SPBU). On the other hand, villages that are more than 15 km from distribution gas stations, do not experience a significant impact on reducing transportation cost.